The tango of two deadly sins the social-functional relation of envy and pride [article]. - Lange, Jens; Crusius, Jan
Envy stems from a social comparison with a superior standard. Its 2 distinct forms are directed at changing this situation in different ways, either by becoming as successful as the envied person (in benign envy) or by lowering the envied person?s advantage (in malicious envy). In essence, envy is thus a social phenomenon. Nevertheless, most previous research has focused on its underlying intrapersonal processes, overlooking envy?s interpersonal core. In contrast, we show in 6 studies (N = 1,513) that envy and pride are intertwined in a social-functional relationship. Envy and pride often co-occur (Study 1) and pride displays enhance envious feelings (Studies 2 and 3). Specifically, authentic (success attributed to effort) and hubristic pride (success attributed to talent) modulate envious intentions and behavior toward their benign and malicious form (Study 2 to 6). This effect is mediated via liking, perceived prestige, and perceived dominance (Study 4). In accordance with a social-functional approach, the effects emerge only when authentic and hubristic pride are expressed by the superior person and not when the respective information about the superior person?s feelings is simply available in the environment (Study 5). These effects are present when participants recall envy situations (Study 1), when they imagine being in a competitive situation (Studies 3, 4, and 5), or when envy is elicited in situ (Studies 2 and 6). Our findings show the value of studying envy as a social phenomenon and open up numerous avenues for research on envy at the interpersonal and intergroup level. -- (from the authors)